Christianity and sport - Gojković Goran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2017)
In this paper we will demonstrate, relying on theology, that Christianity, i.e. ascetic experience of the Church and sport are two sides of the same coin which is reflected in community or, rather, communion (When Christianity is concerned), or team work towards the goal when it comes to sport.